2021
DOI: 10.3390/ani11061774
|View full text |Cite
|
Sign up to set email alerts
|

Miúda (Nopalea cochenillifera (L.) Salm-Dyck)—The Best Forage Cactus Genotype for Feeding Lactating Dairy Cows in Semiarid Regions

Abstract: This study aimed to investigate the effects on nutrient intake and digestibility, milk yield (MY) and composition, milk fatty acids profile, and microbial protein synthesis caused by feeding lactating dairy cows four different forage cactus genotypes. Eight Girolando cows (5/8 Holstein × 3/8 Gyr), weighing 490 ± 69.0 kg (means ± standard deviation), and producing 15.5 ± 1.0 kg/d of milk during pretrial were distributed to two contemporaneous 4 × 4 Latin squares. The cows were fed a total mixed ration composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Soluble NSPs can increase the viscosity of the digestate and reduce nutrient digestibility [43]. The superiority in DMDC of Miúda CPM can be attributed to the sugar and starch contents [7,36] since the concentration of these carbohydrates contributes considerably to high palatability, which explains the higher dry matter digestibility of that variety, corroborating the results represented in Figure 2.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Soluble NSPs can increase the viscosity of the digestate and reduce nutrient digestibility [43]. The superiority in DMDC of Miúda CPM can be attributed to the sugar and starch contents [7,36] since the concentration of these carbohydrates contributes considerably to high palatability, which explains the higher dry matter digestibility of that variety, corroborating the results represented in Figure 2.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the AME value of Miúda CPM was positively affected by the high contents of non-fiber carbohydrates, mainly starch, being the main source of energy for birds [7,36,40,41]. These results are attributed to the higher intake of non-fiber carbohydrates, which consequently provided higher energy intake [42].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In general, energy is the most limiting "nutrient" for animal production. [72] showed that O. ficus-indica and N. cochenillifera has an average ME content of 2.34 Mcal/kg DM. In Table 8 presents the estimates of DM productivity/ha of various forages that are commonly recommended for semiarid regions.…”
Section: Spinelles Cactus As Forage and Desertification Mitigationmentioning
confidence: 99%